2020
DOI: 10.3389/fendo.2020.573452
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Differences in the Association of Metabolically Healthy Obesity With Hyperuricemia and a Network Perspective in Analyzing Factors Related to Hyperuricemia

Abstract: Background Although obesity is a well-known risk factor for hyperuricemia, it remains unclear whether obese subjects with metabolically healthy status have a decreased the risk of hyperuricemia and whether sex modifies the association of metabolically healthy obesity (MHO) with hyperuricemia risk. We aimed to investigate the sex-specific association between MHO and other obesity phenotypes and hyperuricemia, and to use Bayesian networks to determine and visualize the interactions among hyperuricem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…Consistent with our results, L.-K. Chen et al claimed a positive association between serum UA and HOMA-IR in older women but not in men among a Taiwan population (46). Another study revealed a sex-difference association between metabolically healthy obese status and hyperuricemia (47). Further studies are warranted to explore the sex-related roles of IR in hyperuricemia.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our results, L.-K. Chen et al claimed a positive association between serum UA and HOMA-IR in older women but not in men among a Taiwan population (46). Another study revealed a sex-difference association between metabolically healthy obese status and hyperuricemia (47). Further studies are warranted to explore the sex-related roles of IR in hyperuricemia.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that obesity and its phenotypes are significantly associated with the risk of hyperuricemia, and the relationship are sex-specific and age-specific differences ( 29 31 ). In the Chinese population, Tian et al suggested that the MHOO phenotype was significantly associated with the risk of hyperuricemia only in women and not in men from the China Health and Nutrition Survey ( 30 ). Yu et al found that MUOO, in comparison with MHOO, was significantly associated with hyperuricemia in Chinese adults ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study further showed that hyperuricemia was signifficantly associated with MetS-related variables such as elevated blood pressure, abdominal obesity, and elevated TG but not elevated fasting glucose and reduced HDL-C, which is slightly different from other studies. Many studies have demonstrated a strong association between SUA and various MetS-related components, but the association could be differed by study objects (25,34,35). Kim et al discovered that hyperuricemia was positively connected with the remaining MetS components except for hyperglycemia in male patients, and hyperuricemia was favorably correlated with all MetS components in female patients (25).…”
Section: Hyperuricemia Was Positively Correlated With the Mets Compon...mentioning
confidence: 99%